Effectiveness of aerogel roofing system on temperature reduction in Malaysian residential buildings - Nuruddin, M.F. (Medwell Journals, 2017)
Malaysia is located in the tropical region near to the equator, exposed to long hours of sunshine and experiences high temperature and relative humidity throughout the year. In tropical countries, 75 of the heat generation in a house come from the roof. Based on previous research, installing insulation on roof has successfully given positive impacts on indoor temperature reduction. It was discovered that aerogel is the current best solid insulation material where it has the lowest thermal conductivity of 0.02 W/m.K. However, current usage of aerogel was only restricted in aeronautics, military, vessels and piping insulation. The efficiency of aerogel as roof insulation material was simulated using Ecotect Analysis 2011 and to demonstrate the real condition, the indoor and outdoor temperature of three small-scale houses was measured. The results obtained from all stages of this research shows that aerogel induced the highest outdoor-indoor temperature differences up to 8.1°C compared to aluminium foil and stone wool. From the energy saving cost analysis, it was shown that aerogel reduced the energy cost in comparison with non-insulated roof the highest by 89. These results support the effectiveness of aerogel as roof insulation in residential building. It is recommended to demonstrate the installation of aerogel in real house and further analysis on cost benefit analysis to be done in future research. © Medwell Journals, 2017.